Knowledge On Drug Safety and Drug Utilization During Pregnancy: A Review of Systematic Reviews and Meta- Analyses - Anshar Timur Samudra; Antonius Adji Prayitno Setiadi; Sylvi Irawati (Universitas Malahayati Lampung, 2025)
ABSTRACT Drug use all through pregnancy can be beneficial or dangerous to the expectant mother, her fetus, and the baby. Some drugs have a risk of causing disability or death. Pregnant women's lack of knowledge about the harms of drug use during pregnancy can affect the use of these drugs during pregnancy. This study aims to review systematic reviews and meta-analyses regarding knowledge and use of medications during pregnancy in pregnant women. The design of this study is a scoping review using the PubMed database. The studies reviewed are systematic reviews and meta-analyses published in 2014-2024. Of the 1658 search results, five studies met the inclusion criteria. Four systematic reviews discussed drug utilization during pregnancy, and one systematic review addressed the knowledge of pregnant women regarding the use of drugs during pregnancy. The prevalence of antibiotic consumption during pregnancy ranges from 0.04 to 90%. While the prevalence of herbal medicine use in pregnant women varies between 12% and 93%. As many as 93.3% of pregnant women do not know enough about medicines and have gaps in knowledge or information about medicines, whether prescription drugs, over-the-counter drugs, or herbal medicines. Pregnant women's knowledge is also limited about the risks associated with polypharmacy in the first trimester of pregnancy, and there is a relationship between polypharmacy during pregnancy and an increased risk of congenital malformations. In conclusion, the prevalence of herbal medicine and antibiotic use during pregnancy is still relatively high. Most pregnant women do not have a good level of knowledge regarding the use of these medicines during pregnancy. Keywords: Drug Utilization, Knowledge, Pregnancy